\(\sqrt{7x^2+25x+19}-\sqrt{x^2+2x-35}=7\sqrt{x+2}\)
giải phương trình \(\sqrt{x}+\sqrt{x+7}+2\sqrt{x^2+7x}=35-2x\)
Giải phương trình vô tỉ :
a) \(\sqrt{7x^2+25x+19}-\sqrt{x^2-2x-25}=7\sqrt{x+2}\)
b) \(\sqrt{4x^2+24x+35}-\sqrt{x^2+3x+2}=\sqrt{x^2+7x+12}\)
1)\(7\sqrt{3x-7}+\left(4x-7\right)\sqrt{7-x}=32\)
2)\(4x^2-11x+6=\left(x-1\right)\sqrt{2x^2-6x+6}\)
3)\(9+3\sqrt{x\left(3-2x\right)}=7\sqrt{x}+5\sqrt{3-2x}\)
4)\(\sqrt{2x^2+4x+7}=x^4+4x^3+3x^2-2x-7\)
5)\(\frac{6-2x}{\sqrt{5-x}}+\frac{6+2x}{\sqrt{5+x}}=\frac{8}{3}\)
6)\(2\left(5x-3\right)\sqrt{x+1}+\left(x+1\right)\sqrt{3-x}=3\left(5x+1\right)\)
7)\(\sqrt{7x+7}+\sqrt{7x-6}+2\sqrt{49x^2+7x-42}=181-14x\)
help me now
\(\left(x-x^2\right)\left(\sqrt{x-2}+2\right)=2x^3-5x^2+5x-2\)
\(\sqrt{2x-3+\sqrt{4x-7}}+\sqrt{2x+9+5\sqrt{4x-7}}=4\sqrt{2}\)
\(\left(\sqrt{3x+1}-\sqrt{x+2}\right)\left(\sqrt{3x^2+7x+2}+9\right)=6x-3\)
Giải phương trình
a) \(\sqrt{x-2}=\sqrt{x^2-4x+3}\)
b) \(2\left(\sqrt{\dfrac{x-1}{4}}-3\right)=2\sqrt{\dfrac{4x-4}{9}}-\dfrac{1}{3}\)
c) \(\dfrac{9x-7}{\sqrt{7x+5}}=\sqrt{7x+5}\)
d) \(4+\sqrt{2x+6-6\sqrt{2x-3}}=\sqrt{2x-2+2\sqrt{2x-3}}\)
Tìm `ĐKXĐ`:
\(\sqrt{\dfrac{-5}{6+x}}\)
\(\sqrt{\dfrac{-2}{6-x}}\)
\(\sqrt{\dfrac{-x+3}{-6}}\)
\(\sqrt{\dfrac{7x-1}{-9}}\)
\(\sqrt{\dfrac{x+2}{x^2+2x+1}}\)
\(\sqrt{\dfrac{x-2}{x^2-2x+4}}\)
giải phương trình:
\(a,\sqrt{2x-3}+\sqrt{5-2x}=3x^2-12x+14\)
\(b,x^2-2x-x\sqrt{x}-2\sqrt{x}+4=0\)
\(c,3x^2+21x+18+2\sqrt{x^2+7x+7}=2\)
\(d,\frac{2\sqrt{2}}{\sqrt{x+1}}+\sqrt{x}=\sqrt{x+9}\)
\(c,\sqrt{3x^2-5x+1}-\sqrt{x^2-2}=\sqrt{3\left(x^2-x-1\right)}-\sqrt{x^2-3x+4}\)
Tìm x để các biểu thức sau có nghĩa :
a) \(\sqrt{5x-3}\)- \(\sqrt{x+4}\)
b)\(\sqrt{\frac{4-7x}{2x+3}}\)
c) \(\sqrt{3x^2-7x+4}\)
d) \(\frac{\sqrt{x^2+2x-35}}{\sqrt{4x^2-12x+9}}\)